HIRING-HIRING :EKSISTENSI SASTRA LISAN MASYARAKAT KOMERING - Fahira, Setya; Syawaluddin, Mohammad; Khudin, Sholeh (Tanjak: Sejarah dan Peradaban Islam, 2023)
This article is entitled "The Existence of Hiring-Hiring as Oral Literature in the Komering Society of East OKU Regency" where the research was conducted in the village of Mengulak, Madang Suku I sub-district. The problems in this research are: How does Hiring-Hiring exist in the life of the Komering people in Mekulak village, OKU Timur district. The research method used is a qualitative method with a historical approach which in practice goes through four stages of historical research, namely heuristics, source criticism, interpretation, and historiography. The data analysis process goes through three stages, namely data reduction, data presentation, and drawing conclusions. Sources of data in this study were obtained from observational studies, documentation, and interviews. The functionalism theory of Brownislaw Malinowski is used to ensure the existence of a culture, in this case the Hiring-Hiring tradition. The results of the study show that Hiring-Hiring as an oral tradition in the Komering community in Mengulak village has been going on for a long time, and has been inherited from generation to generation, at least the closest period known to the practicing community was in the 19th century, namely along with the development of the pantun concept in the entire Malay Universe. The condition of Hiring-Hiring as a tradition as well as Komering oral literature can be said to be on the verge of extinction, but traditional leaders are trying to return to the culture of Hiring-Hiring on Komering land, especially in Mengulak Village, Madang Suku I District, by demonstrating it in various ceremonies and events, such as traditional ceremonies, weddings, circumcisions, cultural arts performances at schools and so on.